Robust visual cortex evoked potentials (VEP) in Gnat1 and Gnat2 knockout mice - Flood, Michael D.; Veloz, Hannah L. B.; Hattar, Samer; Carvalho-de-Souza, Joao L. (Frontiers in Cellular Neuroscience, 2022)
Intrinsically photosensitive retinal ganglion cells (ipRGCs) express the photopigment melanopsin, imparting to themselves the ability to respond to light in the absence of input from rod or cone photoreceptors. Since their discovery ipRGCs have been found to play a significant role in non-image-forming aspects of vision, including circadian photoentrainment, neuroendocrine regulation and pupillary control. In the past decade it has become increasingly clear that some ipRGCs also contribute directly to pattern-forming vision, the ability to discriminate shapes and objects. However, the degree to which melanopsin-mediated phototransduction, versus that of rods and cones, contributes to this function is still largely unknown. Earlier attempts to quantify this contribution have relied on genetic knockout models that target key phototransductive proteins in rod and cone photoreceptors, ideally to isolate melanopsin-mediated responses. In this study we used the Gnat1-/-; Gnat2 cpfl3/cpfl3 mouse model, which have global knockouts for the rod and cone α-transducin proteins. These genetic modifications completely abolish rod and cone photoresponses under light-adapted conditions, locking these cells into a “dark” state. We recorded visually evoked potentials in these animals and found that they still showed robust light responses, albeit with reduced light sensitivity, with similar magnitudes to control mice. These responses had characteristics that were in line with a melanopsin-mediated signal, including delayed kinetics and increased saturability. Additionally, we recorded electroretinograms in a sub-sample of these mice and were unable to find any characteristic waveform related the activation of photoreceptors or second-order retinal neurons, suggesting ipRGCs as the origin of light responses. Our results show a profound ability for melanopsin phototransduction to directly contribute to the primary pattern-forming visual pathway.